The Saddam tapes the inner workings of a tyrant's regime, 1978-2001 - Woods, Kevin M.; Palkki, David D.; Stout, Mark (Cambridge University Press, 2011)
This study presents the annotated transcripts of Iraqi audio recordings of meetings between Saddam Hussein and his inner circle. The original study, and the larger body of captured recordings on which it rests, will provide researchers with important insights into the inner-workings of the regime and, it is hoped, the nature of authoritarian regimes more generally.